Assessing Preceptor and Student Perceptions of Remote Advanced Pharmacy Practice Experience Learning during the COVID-19 Pandemic - S. Lena Kang-Birken; Elaine J. Law; Yong S. K. Moon; Audrey J. Lee; Andrew L. Haydon; Allen Shek (MDPI AG, 2022)
The coronavirus disease 2019 pandemic created a major shift in learning modalities in the Advanced Pharmacy Practice Experience program. This descriptive study aimed to evaluate preceptor and student perceptions of remote learning experiences and student practice readiness upon completion of remote rotations. Preceptors and students who participated in partial to full remote experiential rotations between 17 August 2020 and 26 March 2021 were invited to complete an on-line survey. A cross-sectional survey consisted of closed-ended questions using a 5-point Likert scale assessing perception on adaptability, effectiveness of remote learning in advancing practice knowledge and skills, and confidence in students' practice readiness. A total of 29 preceptors and 43 students completed the survey (response rates of 67% and 57%, respectively). Approximately 70% of the remote rotations were practice-based, with ambulatory care representing the most frequently reported rotation by preceptors (38%) and students (28%). A high level of confidence in preceptor perception of their ability to adapt and provide effective remote experiences (average 4.28) matched with the students' high level of confidence with their preceptors' abilities (86% agree or strongly agree). Upon the completion of remote rotations, both preceptors and students felt confident in student practice readiness based on student ability to design and initiate individualized patient care plans or complete projects using evidence-based resources (79% and 86%, respectively). Most preceptors (69%) reported that students achieved the rotation objectives at the same level as students engaged in-person experiences. The limitations of remote learning included the absence of direct interactions. Overall, both preceptors and students reported achieving practice readiness with remote experiential learning experiences and felt the remote activities should be continued post-pandemic.